PBK 91 - 95 : Vijf Jaar Praktijkbureau Beeldende Kunstopdrachten. - Crouwel, Wim; Grosfeld, Govert; Sanders, Martijn; van Gestel, Tom; van Tienhoven, Ronald; PBK - Praktijkbureau Beeldende Kunstopdrachten, Amsterdam (Amsterdam : Mondriaan Stichting, 1995)
Shanabrook, Stephan ; Hooykaas & Stansfield ; Körmeling, John ; Giezen, Krijn ; Schouten, Harold ; Drummen, Suzan ; van Hanegem, Ab ; de Zeeuw, Mirjam ; Puckey, Thom ; Roothaan, Steef ; Ahearn, John ; Torres, Rigoberto ; Lehnerer, Thomas ; Gudmundsson, Sigurdur ; Boezem, Marinus ; Descombes, Georges ; Pistoletto, Michelangelo ; Kaap, Gerald Van Der ; Struycken, Peter ; Vendel, Paul ; Dumas, Marlene ; Wier, Jan ; van der Linden, Thomas ; Blom, Ansuya ; Ruggiu, Roberto ; Utkin, Ilya ; Brodsky, Alexander ; Vandevelde, Ludwig ; Zegveld, Peter ; Visch, Henk ; Goudsbloem, Karel ; Höfer, Candida ; Katase, Kazuo ; Copers, Leo ; Weeber, Carel ; Struycken, Peter ; Zaugg, Rémy ; Mik, Aernout ; Mark, Arno Van der ; Rombouts & Droste ; Blum, Andrea ; Greene, Robert ; de Reus, Maarten ; Douglas, Stan ; Kosuth, Joseph ; Rückriem, Ulrich ; Art & Language ; Zegers, Ben ; Toebosch, Moniek ; de Wint, R.W. van ; Libeskind, Daniel ; Krause, Till ; Gudjonsdottir, Anna ; van Tienhoven, Ronald ; Kawamata, Tadashi ; De 4 Evangelisten ; Eikelenboom, Alfred ; Tiong Ang ; Müller, Pjotr ; Ruygrok, Marc ; van Golden, Daan
Engels & Nederlands
boek